2013
DOI: 10.1007/s11999-013-3058-8
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde Versus Antegrade Intramedullary Nailing of Gunshot Diaphyseal Femur Fractures

Abstract: Background The use of retrograde nailing for gunshot wound femur fractures is controversial due to concerns of knee sepsis after this procedure since the knee is entered to introduce the nail into the canal. Questions/purposes We compared retrograde and antegrade nailing for gunshot femur fractures to determine whether (1) knee sepsis or other adverse events were more likely to complicate procedures using retrograde nails, (2) there were differences in surgical time or blood loss, and (3) there were difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 11 publications
0
7
0
1
Order By: Relevance
“…Ricci et al showed that both antegrade and retrograde nailing of femoral shaft fractures go on to successful union approximately 89% and 88% of the time, respectively, 23 and reoperation because of fracture nonunion is relatively uncommon when femoral shaft fractures are treated with intramedullary devices. Dougherty et al 24 also found no differences about operative time, blood loss, or radiographic union when comparing retrograde with antegrade nailing for ballistic femur fractures. Our results showed ballistic femoral shaft fractures with a 4% nonunion rate that closely resembled blunt closed fractures (4.0% vs. 5.0%) and was less common than the blunt open fractures, which had a nonunion rate of 9.0%.…”
Section: Discussionmentioning
confidence: 98%
“…Ricci et al showed that both antegrade and retrograde nailing of femoral shaft fractures go on to successful union approximately 89% and 88% of the time, respectively, 23 and reoperation because of fracture nonunion is relatively uncommon when femoral shaft fractures are treated with intramedullary devices. Dougherty et al 24 also found no differences about operative time, blood loss, or radiographic union when comparing retrograde with antegrade nailing for ballistic femur fractures. Our results showed ballistic femoral shaft fractures with a 4% nonunion rate that closely resembled blunt closed fractures (4.0% vs. 5.0%) and was less common than the blunt open fractures, which had a nonunion rate of 9.0%.…”
Section: Discussionmentioning
confidence: 98%
“…It has been indicated that intramedullary nail fixation is the preferred choice for treating femur fractures if complete weight bearing is a consideration. [3][4][5][6][7][8][9][10] The present study shows the treatment of Femoral fracture using an intramedullary nailing device which was designed and manufactured by Kaulmed private limited, India.…”
Section: Discussionmentioning
confidence: 98%
“…Intramedullary nail fixation has shown comparable time to union for low-energy ballistic diaphyseal femur when compared with closed fractures 51-53 . Retrograde nail fixation has likewise demonstrated similar success without evidence of the theoretical increased risk of knee septic arthritis after low-energy ballistic femur fractures 54,55 . As with all intramedullary fixation techniques, assessment of length and rotation is critical and may present specific challenges in the ballistic population with higher rates of postoperative rotational and length errors 56 .…”
Section: Long-bone Injuriesmentioning
confidence: 99%